Microstructure and interfaces of thin film capacitors on base metal foils - T. Dechakupt (2018)
The microstructure and interface quality of chemical solution deposited barium titanate thin films on Ni foil were studied. Cross-sectional transmission electron microscopy shows that a ∼200 nm thick barium titanate film annealed in a controlled oxygen partial pressure consists of equiaxed grains with grain size range of 24-75 nm (∼ 42 nm average). NiO was detected after re-oxidation by X-ray diffraction, but not by transmission electron microscopy, suggesting that the oxide is not a continuous barrier layer, but is spatially distributed in the films. Oxygen non-stoichiometry and the existence of C in barium titanate films were observed by electron energy loss spectrometry. In addition, it was found that there is a 5-8 nm thick Ni-Ba alloy developed at the interface between the barium titanate film and Ni foil. © 2008 Trans Tech Publications, Switzerland.